2019
DOI: 10.1002/elps.201800431
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring phase transition of aqueous biomass model substrates by high‐pressure and high‐temperature microfluidics

Abstract: Aqueous‐Phase Reforming (APR) is a promising hydrogen production method, where biomass is catalytically reformed under high pressure and high temperature reaction conditions. To eventually study APR, in this paper, we report a high‐pressure and high‐temperature microfluidic platform that can withstand temperatures up to 200°C and pressures up to 30 bar. As a first step, we studied the phase transition of four typical APR biomass model solutions, consisting of 10 wt% of ethylene glycol, glycerol, xylose or xyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…), which is reminiscent of our previous work. 59 The additional 15°C above the nominal boiling temperature is indicative of superheating, which is also consistent with the observed boiling mechanism. In contrast, in devices with micropits, the first vapor bubbles already formed at 85°C (Fig.…”
Section: Controlling Bubble Formationsupporting
confidence: 82%
See 1 more Smart Citation
“…), which is reminiscent of our previous work. 59 The additional 15°C above the nominal boiling temperature is indicative of superheating, which is also consistent with the observed boiling mechanism. In contrast, in devices with micropits, the first vapor bubbles already formed at 85°C (Fig.…”
Section: Controlling Bubble Formationsupporting
confidence: 82%
“…DRIE-etching of silicon gives rise to defects on the silicon walls, or so-called scallops, which can also be hydrophobic due to the presence of fluorocarbon residues from the dry-etching. 59 Examination of both the micropits and the silicon microchannel wall using highresolution SEM demonstrated that the micropits were very similar in size as the etching defects, around 2 μm (see ESI-7 †), so that both structures could equally act as bubble nucleation sites by lowering the thermodynamic barrier for nucleation.…”
Section: Bubble Shapementioning
confidence: 99%
“…At low protrusion angles (below 45°) positive slip lengths were expected, and negative slip at higher angles . The low temperature value (525 K) corresponded to a typical APR reaction temperature , whereas the upper temperature limit (725 K) refers to the maximum temperature, at which our microreactor can operate .…”
Section: Methodsmentioning
confidence: 96%
“…). This 2D geometry was derived from a previously described silicon/glass microfluidic device . Briefly, a 250‐µm deep fluidic channel was created in a silicon substrate and covered by a glass top layer.…”
Section: Methodsmentioning
confidence: 99%